(untitled) (Revista de Artes Marciales Asiáticas, 2017)
With the changes in lifestyle, eating habits and new training methodologies, it becomes important that scientific research fills gaps in anthropometric and nutritional knowledge fields, with the purpose of improving martial arts and combat sports athletes’ physical fitness and performance during competition and training. This study aimed to assess the nutritional status and knowledge in martial arts fighters, and relate it to their perception of body image. We evaluated 37 male fighters, who practiced different forms of martial arts in two academies in west São Paulo. To measure the nutritional status body weight, height and skinfolds were assessed. The perception of body image and nutritional knowledge were also assessed. The sample showed an average of 25 ± 5 years, 84.4 ± 15.78 kg, 1.76 ± 0.07 m and fat percentage of 14.12 ± 5.46. The mean body mass index was 26.95 ± 3.75 kg/m², which means they were overweight. 70.27% of the fighters had moderate nutritional knowledge, 24.32% low knowledge and the remaining 5.41% high knowledge. In relation to the nutritional status, the fighters were mostly overweight and had fat percentage below average, with high body image dissatisfaction and moderate nutritional knowledge.